2002
DOI: 10.1095/biolreprod.102.004812
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Preimplantational Development of Porcine Parthenogenetic Diploids Relative to the Existence of Amino Acids In Vitro1

Abstract: The present study was designed to investigate the effects of amino acids on the in vitro development of porcine parthenogenetic diploids that were produced by electrostimulation (El-St) and cytochalasin B treatment of in vitro-matured oocytes. The culture medium for development, based on Whitten medium, contained 0.5 mg/ml of hyaluronic acid (mWM), and a two-step culture system in which 290 mOsmol before the 4-cell stage (48 or 72 h after El-St) and, subsequently, 256 mOsmol up to the blastocyst stage (mWMs) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
43
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 51 publications
4
43
1
1
Order By: Relevance
“…Our results suggest that the presence of EAA at a low concentration during the first 72 h of culture is not overtly inhibitory although neither were the EAA beneficial and there is evidence that they inhibit the development of cleavage stage mouse [20] and, under certain conditions, pig embryos [10]. As such, we decided to include the EAA at a 1:100 dilution in our culture system from day 3 onwards only.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Our results suggest that the presence of EAA at a low concentration during the first 72 h of culture is not overtly inhibitory although neither were the EAA beneficial and there is evidence that they inhibit the development of cleavage stage mouse [20] and, under certain conditions, pig embryos [10]. As such, we decided to include the EAA at a 1:100 dilution in our culture system from day 3 onwards only.…”
Section: Discussionmentioning
confidence: 97%
“…Ammonium in the culture medium has been shown to be detrimental to the in vitro development of mouse embryos [21,22] and it has been suggested that a decrease in the rate of ammonium accumulation may be partially responsible for the improved development seen by reducing the concentrations of EAA in the culture mouse embryos [11]. However, further research is required to determine how much these factors contribute to the effect seen in our experiment.Our results suggest that the presence of EAA at a low concentration during the first 72 h of culture is not overtly inhibitory although neither were the EAA beneficial and there is evidence that they inhibit the development of cleavage stage mouse [20] and, under certain conditions, pig embryos [10]. As such, we decided to include the EAA at a 1:100 dilution in our culture system from day 3 onwards only.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, diploid parthenotes have frequently been used to study early development in the pig (Van Thuan et al 2002). In the present study, we determined the effects of polyvinyl alcohol (PVA), fetal bovine serum (FBS) and BSA on the developmental ability and apoptosis of porcine 2-cell parthenotes at 24 h after activation (before embryonic genome activation) and late 4-cell diploid parthenotes at 72 h after activation (after embryonic genome activation) developing in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, addition of EAAs and NEAAs to NCSU-23 had no effect on the in vitro development of IVF and SCNT embryos. However, previous studies have suggested that addition of EAAs and NEAAs to the culture medium promotes the development of embryos in mice [42], cows [43,44] and pigs [22,45]. These previous studies reported that EAAs and NEAAs are components that promote embryo development when cultured in media containing lactate and pyruvate as energy substrates.…”
mentioning
confidence: 99%